Functional skull asymmetries in Carollia perspicillata (Phyllostomidae Gray, 1825: Carollinae) - Parés-Casanova, Pere M.; Otin, Gerard (Acta Biologica Szegediensis, 2020)
Analysing asymmetry in wild or domestic species enables the evaluation of the morphological responses to functional requirements and/or stress. This report is a study of the cranial asymmetry of Seba's short-tailed bat Carollia perspicillata by means of geometric morphometric techniques. We studied three types of bilateral asymmetries -ﬂuctuating asymmetry, directional asymmetry and antisymmetry- using 15 skull landmarks on dorsal aspect of 45 skulls of Carollia perspicillata (21 males and 24 females) from different localities in Colombia. Directional asymmetry appeared to be significant and clearly higher than ﬂuctuating asymmetry, with the braincase presenting the larger variance. There were no differences between sexes. Echolocation has a great anatomical effect on the bat cranium, and this would explain detected asymmetry.